Amelanotic melanoma of the head and neck: analysis of tumor characteristics from the National Cancer Database. (11th October 2020) - Huayllani, Maria T.; Boczar, Daniel; Saleem, Humza Y.; Spaulding, Aaron C.; Bagaria, Sanjay P.; Lu, Xiaona; Kassis, Salam; Perdikis, Galen; Forte, Antonio Jorge
Abstract: Background: Amelanotic melanoma is an extremely rare subtype of cutaneous melanoma. The tumor characteristics are still not well understood, especially for those located in the head and neck. Methods: Tumor characteristics of patients diagnosed with amelanotic melanoma of the head and neck (AMHN) from January 1, 2004, to December 31, 2015, were analyzed by querying the National Cancer Database. Characteristics of AMHN were subsequently compared with common malignant melanoma of the head and neck (CMMHN). Results: Three hundred and sixty‐eight patients were diagnosed with AMHN, and 69, 267 were diagnosed with CMMHN. Of those with AMHN, 128 (34.8%) had melanoma located on the scalp and neck, and 172 (46.7%) were diagnosed with an early disease stage (i.e., 0, I, or II). When compared with CMMHN, patients with AMHN were more likely to be diagnosed after 80 years of age (25.3% vs. 18.2%; odds ratio [OR], 3.28; 95% CI, 1.09–9.84; P  = 0.03), when Breslow depth was between 2.01 and 4.00 mm (28.5% vs. 6.5%; OR, 1.92; 95% CI, 1.15–3.19; P  = 0.01), when ulceration was present (36.7% vs. 9.0%; OR, 1.99; 95% CI, 1.34–2.97; P  = 0.001), and when mitotic count was 1 or more/mm 2 (40.5% vs. 12.8%; OR; 2.53; 95% CI, 1.09–5.89; P  = 0.03). No statistical difference was found for sex, specific location, stage, or lymph node involvement. Conclusion: Our study determined that AMHN is associated with older age, increased Breslow depth, presence of ulceration, and greater mitotic count when compared with CMMHN.